Tikki Tikki Tembo - Mosel, Arlene; Lent, Blair (New York Scholastic Inc., 1968)
When the eldest son fell in the well and most of the time getting help was spent pronouncing the name of the one in trouble, the Chinese, according to legend, decided to give all their children short names.
Adaptation of a Chinese folktale.
Keywords: Folklore -- China